High-performance lignin-based non-isocyanate polyurethane adhesive
Through the transesterification-aldehyde amine chemical method, the synthesis process of non-isocyanate polyurethane is simplified, the complex and cost-effective synthesis in the prior art is solved, and a bulk lignin-based non-isocyanate polyurethane adhesive with excellent adhesive properties and resistance is prepared.
Patent Information
- Application Number
- CN202411763957.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
The existing non-isocyanate polyurethane synthesis route is complex, involving high-pressure conditions and high-cost cyclic carbonate structures, and its application fields are limited, making it difficult to be used for the preparation of high-performance adhesives.
By dissolving lignin in an alkaline aqueous solution, a high-performance lignin-based non-isocyanate polyurethane adhesive was prepared by dissolving lignin in an alkaline aqueous solution for transesterification reaction, followed by polycondensation reaction with polyamine, and adding a crosslinking agent for crosslinking modification.
The synthesis process is simplified, the cost is reduced, and the multi-step solvent removal step is avoided, and bulk wood adhesives with excellent adhesive properties, organic solvent resistance and low temperature resistance are prepared.
Smart Images

Figure CN119614131A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive preparation, and in particular to a high-performance lignin-based non-isocyanate polyurethane adhesive. Background Art
[0002] Polyurethane (PU) has high strength and excellent weather resistance and is widely used in many fields such as wood processing, automotive industry, aerospace, etc. The traditional synthesis method of PU includes the polycondensation of diisocyanates (or polyisocyanates) and diols (or polyols). However, isocyanates are highly toxic and carcinogenic, and can penetrate into the human body through direct contact with the respiratory tract, eyes and skin, causing serious damage to the human body. In addition, the preparation process of isocyanates also involves the use of highly dangerous phosgene. Therefore, some isocyanate-free polycyanate synthesis methods have been developed in recent years. The emergence of non-isocyanate polyurethane (NIPU) avoids the use of dangerous phosgene-based isocyanates, making it a safer and more environmentally sustainable alternative to traditional polyurethane. The synthesis strategies of NIPU developed so far have harsh conditions, such as complex steps involving high temperature and high pressure. Among them, the aminolysis reaction between amines and cyclic carbonates has been widely studied. However, due to the shortcomings of limited types of cyclic carbonate monomers, harsh synthesis conditions, and high cost, the application field of NIPU has been severely limited.
[0003] In recent decades, under the influence of the concept of green chemistry, research on the use of biomass-derived monomers to replace petrochemicals to prepare green and environmentally friendly materials has been increasing. Lignin is the most abundant natural polyphenol on the earth, with a complex non-polar aromatic skeleton structure and polar side chain structure. At present, the effective utilization of lignin is seriously insufficient, and most of it is incinerated as a low-grade fuel. There are a large number of different hydroxyl groups in the molecular structure of lignin, so it can be used as a substitute for petroleum-based polyols in the synthesis of polyurethane materials. In the method of synthesizing NIPU using lignin, most of them are to graft cyclic carbonate groups onto lignin, and then use polyamines for ring-opening polymerization to synthesize lignin-based non-isocyanate polyurethanes (LNIPUs). This method involves epoxidation of lignin and insertion of carbon dioxide under high pressure conditions, which is cumbersome and costly. In summary, LNIPUs currently have relatively harsh synthesis conditions, single technical routes and functionality. In this regard, it is an attractive challenge to develop a strategy with simple synthesis methods, environmentally friendly processes, and mild conditions to prepare LNIPUs adhesives with multifunctionality and excellent bonding properties. However, there are few reports on the simple synthesis of high-strength, organic solvent-resistant, and multifunctional LNIPUs adhesives.
[0004] The existing invention CN116323738A discloses a bio-based polymer precursor and a method for synthesizing NIPU and non-isocyanate polyurethane foam (NIPUF) from the precursor. The invention describes mixing kraft lignin with glycerol carbonate, reacting under a nitrogen atmosphere, and oxyalkylating the lignin. The oxyalkylated kraft lignin is then subjected to an ester exchange reaction with dimethyl carbonate to insert a five-membered cyclic carbonate structure into the lignin skeleton. The cyclic carbonated lignin is subjected to a ring-opening addition reaction with a diamine to obtain a lignin-based non-isocyanate polyurethane. The synthesis process in the invention is complicated, involving lengthy steps such as multi-step solvent removal, the cost of the cyclic carbonate raw material is high, and the prepared lignin-based non-isocyanate polyurethane can only be used for foam materials and is difficult to be applied to the adhesive field.
[0005] CN118546360A discloses a method for preparing a catalyst-free and foaming agent-free non-isocyanate polyurethane foam. The patent describes mixing a cyclic carbonate, an amine and a solvent and then allowing the mixture to react; after the reaction is completed, the solvent is removed to obtain a non-isocyanate polyurethane foam. The present invention does not require the addition of any catalyst or foaming agent, and avoids the use of poisonous isocyanates. However, the invention also involves multiple steps such as solvent removal, the cost of the cyclic carbonate raw material is relatively high, and the prepared lignin-based non-isocyanate polyurethane can only be used for foam.
[0006] CN115305041A discloses an environmentally friendly bio-based polyurethane adhesive and a preparation method thereof. The patent uses lignin as a hydrogen bond donor and a quaternary ammonium salt as a hydrogen bond donor to synthesize a low eutectic solvent, adds epoxidized soybean oil to the solvent, introduces carbon dioxide into a reactor for reaction, and synthesizes lignin-modified cyclic carbonate under mild conditions of low temperature and low pressure. Through lignin modification, the hydroxyl content of the cyclic carbonate is increased, the active sites are increased, and benzene rings are introduced, thereby improving the crosslinking degree, adhesive strength, mechanical strength, and heat resistance of the polyurethane adhesive. However, the invention uses epoxidized soybean oil to epoxidize lignin, and then uses carbon dioxide to cyclocarbonate the epoxidized soybean oil-modified lignin under high pressure conditions, which is similar to the traditional method of cyclocarbonating lignin, and also involves lengthy steps such as multi-step solvent removal, and has the problems of relatively harsh synthesis conditions, single technical route and functionality.
[0007] CN111961221A discloses a modified lignin and a preparation method thereof. At 20 to 40°C, lignin and methyl oleate are mixed in a molar ratio of 1:0.5 to 0.8, poured into a zirconium oxide ball mill of a planetary ball mill, and potassium hydroxide of 3 to 5 wt% of the total amount of the mixture is added as an alkaline catalyst. The mixture is ball milled for 80 to 110 minutes, and the modified lignin after transesterification with methyl oleate is poured out from the planetary ball mill for separation. The lignin is mechanochemically modified under solvent-free conditions by high-energy ball milling. However, the modification method of lignin in the invention is mechanochemical modification. As the ball milling time increases, the molecular weight of lignin gradually decreases, destroying the structure of lignin, which has an adverse effect on the subsequent synthesis of adhesives. The reduction in molecular weight will affect the bonding performance. In addition, this transesterification method can only increase the number of hydroxyl groups, and cannot perform double esterification modification on lignin, and cannot synthesize non-isocyanate polyurethane adhesives.
[0008] CN104292446A discloses a method for preparing a degradable polycarbonate lignin-based oil displacement agent monomer, using maleic anhydride-modified lignin as an initiator and an inorganic base as a catalyst, and undergoing a ring-opening polymerization reaction with carbonate at 100-180°C, introducing carbonate groups into lignin molecules, and obtaining a polycarbonate lignin polyol. However, the invention uses maleic anhydride-modified lignin as an initiator, requires the lignin to be modified in advance, and the transesterification reaction conditions are harsh, involving lengthy steps such as multi-step solvent removal.
[0009] Therefore, the existing preparation method of non-isocyanate polyurethane can be found to have the following technical deficiencies: 1. The synthetic routes of non-isocyanate polyurethanes are basically ring-opening addition of cyclic carbonates and amine compounds. However, the synthesis process of cyclic carbonate structure compounds is cumbersome, usually involves high pressure conditions and is costly; 2. The synthesis route of non-isocyanate polyurethane usually involves multiple steps of modification and solvent removal, which is not suitable for the bulk wood adhesive industry and is difficult to apply on a large scale in the short term; 3. There is a lack of research on lignin non-isocyanate polyurethane as an adhesive. The bonding strength is poor, it is not universal for a variety of substrates, and it does not have good weather resistance and solvent resistance, which limits its practical application and promotion. Summary of the invention
[0010] The object of the present invention is to overcome at least one disadvantage of the prior art and provide a high-performance lignin-based non-isocyanate polyurethane adhesive.
[0011] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a high-performance lignin-based non-isocyanate polyurethane adhesive, which is prepared by the following method: 1) dissolving lignin in an aqueous solution with a pH of 9 to 14, heating and stirring to obtain an alkaline lignin solution; 2) adding a non-cyclic diester compound to the alkaline lignin solution obtained in step 1) to carry out an ester exchange reaction to obtain an esterified lignin solution; 3) adding polyamine to the esterified lignin solution obtained in step 2), stirring and mixing to carry out polycondensation reaction, and obtaining a lignin-based non-isocyanate prepolymer solution; 4) Adding a cross-linking agent to the lignin-based non-isocyanate prepolymer liquid obtained in step 3), stirring and mixing the mixture evenly, and discharging the mixture to obtain the high-performance lignin-based non-isocyanate polyurethane adhesive.
[0012] In some examples, the mass ratio of lignin to aqueous solution is 1:3 to 3:1; and / or The mass ratio of the aqueous solution to the non-cyclic diester compound is 1:4 to 3:1; and / or The mass ratio of the non-cyclic diester compound to the polyamine is 1:3 to 4:1; and / or The mass ratio of the polyamine to the cross-linking agent is 1:5 to 5:1.
[0013] In some examples, the transesterification reaction conditions in step 2) are: 40-90° C., reaction time 20-150 min; and / or The polycondensation reaction conditions in step 3) are: 70-99° C., reaction time 20-240 min; and / or The cross-linking reaction conditions in step 4) are: 0-50° C., and the reaction time is 1-30 min.
[0014] In some examples, the lignin in step 1) is selected from at least one of alkali lignin, enzymatic lignin, Kraft lignin, lignin sulfonate, and organic solvent lignin.
[0015] In some examples, the aqueous solution in step 1) is selected from at least one of sodium hydroxide, potassium hydroxide, and calcium hydroxide aqueous solutions.
[0016] In some examples, the structural formula of the non-cyclic diester compound in step 2) is , , wherein R1, R2, R3, R5 are alkyl groups, R4 is -CH2-, and the number of R4 is an integer greater than or equal to 1.
[0017] In some examples, the general structural formula of the polyamine in step 3) is , , , , , , where m, n, s, p, t, and k are all integers greater than or equal to 1.
[0018] In some examples, the cross-linking agent in step 4) has the general structural formula (R7) y -R6-(R8) x , wherein x and y are integers greater than or equal to 1, R7 and R8 are functional groups that can react with amino groups, and R6 is a connecting structure.
[0019] In some embodiments, R7 and R8 are relatively independent aldehyde groups.
[0020] In some examples, the cross-linking agent in step 4) is selected from at least one of glutaraldehyde, glyoxal, malondialdehyde, suberaldehyde, and dialdehyde starch.
[0021] The beneficial effects of the present invention are: Some examples of the present invention adopt a simple one-pot method for the first time to prepare lignin-based non-isocyanate polyurethane adhesives, using lignin as the main raw material, and esterifying lignin with low-cost and highly reactive non-cyclic diester compounds based on ester exchange reaction. Different from the expensive cyclic carbonate structure involved in the current non-isocyanate polyurethane synthesis process, the cumbersome steps of multi-step modification and solvent removal are eliminated. The raw materials used are derived from biomass resources, are non-toxic, environmentally friendly, sustainable and environmentally friendly, with low cost, and simple preparation process, which is conducive to industrial promotion and practical application.
[0022] In some embodiments of the present invention, based on the aldehyde-amine condensation reaction, a cross-linking agent is used to cross-link and modify the lignin-based non-isocyanate prepolymer and perform a hyperbranching reaction to construct a high-density cross-linked network with both soft and hard segments, thereby giving the lignin-based non-isocyanate adhesive excellent bonding properties and organic solvent resistance, thereby obtaining a high-performance lignin-based non-isocyanate polyurethane adhesive.
[0023] In some examples of the present invention, the high-performance lignin-based non-isocyanate polyurethane adhesive has moderate viscosity, which is conducive to the penetration and infiltration of the adhesive into the pores of wood, and has excellent water resistance and hydrophobicity.
[0024] In some embodiments of the present invention, the high-performance lignin-based non-isocyanate polyurethane adhesive has a core structure of polyurethane urethane bonds and forms a dense cross-linking network with a cross-linking agent.
[0025] In some examples of the present invention, the dry bonding strength and Class II wet strength of plywood made of high-performance lignin-based non-isocyanate polyurethane adhesive can reach 1.96MPa and 1.68MPa respectively, while the Class I boiling water resistant bonding strength can reach 1.32MPa, meeting the national use standards for outdoor Class I boards and having excellent permeability on the wood surface.
[0026] In some embodiments of the present invention, the high-performance lignin-based non-isocyanate polyurethane adhesive has excellent bonding performance on metal parts and glass substrates (including stainless steel, iron, copper, carbon fiber, ceramic, aluminum, glass and wood), with a maximum shear strength of up to 10.8 MPa. And the bonding performance is comparable to commercial polyurethane adhesives on the market.
[0027] In some embodiments of the present invention, the high-performance lignin-based non-isocyanate polyurethane adhesive still maintains more than 80% of the shear strength when immersed in various organic solvents and has excellent resistance to organic solvents.
[0028] In some embodiments of the present invention, the high-performance lignin-based non-isocyanate polyurethane adhesive can still maintain a shear strength of more than 70% in a low temperature environment of -50°C and has excellent low temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The invention provides a preparation process for high-performance lignin-based non-isocyanate polyurethane adhesive.
[0030] Figure 2 The bonding mechanism of high-performance lignin-based non-isocyanate polyurethane adhesive.
[0031] Figure 3 is the water absorption rate of different lignin-based non-isocyanate polyurethane adhesives.
[0032] Figure 4 Water contact angles of different lignin-based non-isocyanate polyurethane adhesives.
[0033] Figure 5 Solid-state NMR spectrum of high-performance lignin-based non-isocyanate polyurethane adhesive.
[0034] Figure 6 Infrared spectrum of high performance lignin-based non-isocyanate polyurethane adhesive.
[0035] Figure 7 To investigate the bonding strength and wood damage of wood bonded with different lignin-based non-isocyanate polyurethane adhesives.
[0036] Figure 8 The penetration of different lignin-based non-isocyanate polyurethane adhesives into plywood.
[0037] Fig. 9 Shear strength of high-performance lignin-based non-isocyanate polyurethane adhesives bonding different substrates.
[0038] Fig.10 Comparison of shear strength of high-performance lignin-based non-isocyanate polyurethane adhesive and commercial polyurethane adhesive.
[0039] Fig.11 Shear strength of high-performance lignin-based non-isocyanate polyurethane adhesive after immersion in organic solvents.
[0040] Fig.12 Shear strength of high performance lignin-based non-isocyanate polyurethane adhesive at low temperature. DETAILED DESCRIPTION
[0041] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.
[0042] The first aspect of the present invention provides: A high-performance lignin-based non-isocyanate polyurethane adhesive is prepared simply based on transesterification-aldehyde amine chemistry. The preparation process is as follows Figure 1 As shown, the specific steps include: 1) dissolving lignin in an aqueous solution with a pH of 9 to 14, heating and stirring to obtain an alkaline lignin solution, wherein the aqueous solution is an alkaline aqueous solution capable of dissolving lignin; 2) adding a non-cyclic diester compound to the alkaline lignin solution obtained in step 1) to carry out an ester exchange reaction to obtain a carbonated lignin solution; 3) adding polyamine to the esterified lignin solution obtained in step 2), stirring and mixing to carry out polycondensation reaction, and obtaining a lignin-based non-isocyanate prepolymer solution; 4) Add a cross-linking agent to the lignin-based non-isocyanate prepolymer obtained in step 3), and simply stir and mix to uniformly discharge the material to obtain a high-performance lignin-based non-isocyanate polyurethane adhesive based on ester exchange-aldehyde amine chemistry.
[0043] The aqueous solution is an alkaline solution, which is a good solvent for lignin and can dissolve or disperse lignin well. At the same time, the alkaline condition can promote the transesterification reaction and graft more ester groups at the hydroxyl position of lignin. The selection of the aqueous solution follows the principle that it has good solubility for lignin, non-cyclic diester compounds, polyamines, and cross-linking agents, and does not affect the transesterification and aldehyde amine condensation reactions. In some examples, the aqueous solution is selected from at least one of sodium hydroxide, potassium hydroxide, and calcium hydroxide aqueous solutions. In some examples, the mass ratio of lignin to the aqueous solution is 1:3 to 3:1, preferably 1:2 to 2:1, and more preferably 1:1.
[0044] By adding acyclic diester compounds, lignin and the acyclic diester compounds can undergo an ester exchange reaction to esterify the lignin. The use of low-cost, highly reactive acyclic diester compounds can avoid the use of toxic chemical reagents and cumbersome operating steps. In some examples, the mass ratio of the aqueous solution to the acyclic diester compound is 1:4 to 3:1, preferably 1:3 to 2:1, and more preferably 3:2.
[0045] The use of polyamine can react with the ester group on the lignin esterified with the non-cyclic diester compound to generate a urethane bond, which is conducive to the formation of a high-performance lignin-based non-isocyanate polyurethane prepolymer. In some examples, the mass ratio of the non-cyclic diester compound to the polyamine is 1:3 to 4:1, preferably 2:1 to 1:2, and more preferably 2:3.
[0046] The use of cross-linking agents is based on the polycondensation reaction of aldehyde amines. The cross-linking agent can make the lignin-based non-isocyanate polyurethane prepolymer form a dense cross-linked network, which is conducive to obtaining a multifunctional lignin-based non-isocyanate polyurethane adhesive with strong hydrophobicity, high bonding strength, and resistance to organic solvents. In some examples, the mass ratio of polyamine to cross-linking agent is 1:5 to 5:1, preferably 1:3 to 3:1, and further preferably 3:2. The more the amount of cross-linking agent used, the denser the hyperbranched cross-linked network obtained. The mixing ratio of polyamine and cross-linking agent can be adjusted accordingly according to the specific application.
[0047] By adjusting the temperature of the transesterification reaction, the reaction rate can be adjusted to a certain extent. In order to obtain a suitable reaction rate, in some examples, the esterification reaction conditions in step 2) are: 40-90°C, and not higher than the boiling point of the aqueous solution; preferably 50-60°C, and the preferred reaction time is 20-150 minutes.
[0048] In some examples, the polycondensation reaction conditions in step 3) are: 70-99° C., and not higher than the boiling point of the aqueous solution; preferably 90-95° C., and the preferred reaction time is 20-240 min.
[0049] By adjusting the temperature of the aldehyde-amine cross-linking reaction, the reaction rate can be adjusted to a certain extent. In some examples, the conditions of the step 4) aldehyde-amine cross-linking reaction are: 0-50°C, and the reaction time is 1-30 minutes.
[0050] In some examples, the heating method is selected from constant temperature heating in a water bath or constant temperature heating in an oil bath.
[0051] In some examples, the stirring method is mechanical stirring or magnetic stirring, and the stirring speed is 100 to 500 rpm, preferably 200 to 300 rpm.
[0052] The hydroxyl groups in lignin are used for transesterification reaction. As long as there are sufficient hydroxyl groups in the lignin used, transesterification reaction can occur with non-cyclic diester compounds. In some examples, there are no requirements for the structure, molecular weight, type and source of lignin, and various existing lignins can be used. Depending on the application scenario, the required lignin can be selected. Including but not limited to alkali lignin, enzymatic lignin, Kraft lignin, lignin sulfonate, and organic solvent lignin.
[0053] In some examples, the non-cyclic diester compound in step 2) is selected from at least one of dimethyl carbonate, diethyl carbonate, diethyl succinate, diethyl oxalate, dimethyl oxalate, and dimethyl succinate, but is not limited to one of them, and the general structural formula is , , wherein R1, R2, R3, R5 are alkyl groups, R4 is -CH2-, and the number of R4 is an integer greater than or equal to 1.
[0054] In some examples, the polyamine in step 3) is selected from at least one of polyetheramine, hexamethylenediamine, ethylenediamine, and pentamethylenediamine, but is not limited to one of them, and its general structural formula is , , , , , , where m, n, s, p, t, and k are all integers greater than or equal to 1.
[0055] In some examples, the cross-linking agent in step 4) is selected from at least one of glutaraldehyde, glyoxal, malondialdehyde, suberaldehyde, and dialdehyde starch, but is not limited to one of them. The general structural formula of the cross-linking agent is (R7)y-R6-(R8)x, wherein x and y are integers greater than or equal to 1, R7 and R8 are functional groups that can react with amino groups, and R6 is a connecting group.
[0056] In some embodiments, R7 and R8 are independently aldehyde groups.
[0057] The second aspect of the present invention provides: The first aspect of the present invention describes a simple preparation of a high-performance lignin-based non-isocyanate polyurethane adhesive based on ester exchange-aldehyde amine chemistry, and the applications include adhesives for the manufacture of artificial boards, adhesives for bonding various metal parts, and the like.
[0058] The technical solution of the present invention is further described below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0059] Unless otherwise specified, the reagents used in the examples can be purchased from the market. The room temperature in the examples refers to 20 to 30°C.
[0060] For the sake of comparison, unless otherwise specified, the lignin used in the following examples includes enzymatic lignin from corncob, Kraft lignin, alkali lignin and lignin sulfonate.
[0061] Example 1: Preparation of high-performance lignin-based non-isocyanate polyurethane adhesive (LNIPU-G1) based on transesterification-aldehyde amine chemistry The lignin is selected from lignin sulfonate, the non-cyclic diester compound is selected from dimethyl carbonate, the polyamine is selected from polyetheramine, and the cross-linking agent is selected from 50% glutaraldehyde aqueous solution.
[0062] (1) Add 30 g of lignin sulfonate, 20 g of dimethyl carbonate (DMC), and 30 g of potassium hydroxide aqueous solution with a pH of 9 to 14 to a 500 mL three-necked flask, stir and mix, and react at 50 ° C for 1 h to 2 h under mechanical stirring. Add 30 g of polyetheramine to the above solution, raise the temperature to 90 ° C, and react for 4 h to prepare lignin-based non-isocyanate prepolymer (LNIPUs).
[0063] (2) Weigh 30 g of the lignin-based non-isocyanate prepolymer obtained in step (1) into a plastic cup, add 1.5 g of a 50% glutaraldehyde aqueous solution thereto, and mechanically stir at room temperature until the mixture is uniformly mixed to obtain a lignin-based non-isocyanate polyurethane adhesive. The sample is recorded as LNIPUs-G1.
[0064] Example 2: Preparation of high performance lignin-based non-isocyanate polyurethane adhesive (LNIPU-G2) based on transesterification-aldehyde amine chemistry The lignin is alkali lignin, the non-cyclic diester compound is dimethyl carbonate, the polyamine is polyetheramine, and the cross-linking agent is 50% glutaraldehyde aqueous solution.
[0065] (1) Add 30 g of alkali lignin, 20 g of dimethyl carbonate (DMC), and 30 g of sodium hydroxide aqueous solution with a pH of 9 to 14 to a 500 mL three-necked flask, stir and mix, and react at 50 ° C for 1.5 h to 2 h under mechanical stirring. Add 30 g of polyetheramine to the above solution, raise the temperature to 90 ° C, and react for 4 h to prepare lignin-based non-isocyanate prepolymer (LNIPUs).
[0066] (2) Weigh 30 g of the lignin-based non-isocyanate prepolymer obtained in step (1) into a plastic cup, add 3 g of a 50% glutaraldehyde aqueous solution thereto, and mechanically stir at room temperature until the mixture is uniformly mixed to obtain a lignin-based non-isocyanate polyurethane adhesive. The sample is recorded as LNIPUs-G2.
[0067] Example 3: Preparation of high performance lignin-based non-isocyanate polyurethane adhesive (LNIPU-G3) based on transesterification-aldehyde amine chemistry The lignin is selected from organic solvent lignin, the non-cyclic diester compound is selected from dimethyl carbonate, the polyamine is selected from polyetheramine, and the cross-linking agent is selected from 50% glyoxal aqueous solution.
[0068] (1) Add 30 g of enzymatically hydrolyzed lignin, 20 g of dimethyl carbonate (DMC), and 30 g of sodium hydroxide aqueous solution with a pH of 9 to 14 into a 500 mL three-necked flask, stir and mix, and react at 50 ° C for 1.5 h to 2 h under mechanical stirring. Add 30 g of polyetheramine to the above solution, raise the temperature to 90 ° C, and react for 4 h to prepare lignin-based non-isocyanate prepolymer (LNIPUs).
[0069] (2) Weigh 30 g of the lignin-based non-isocyanate prepolymer prepared in step 1 into a plastic cup, add 4.5 g of a 50% aqueous solution of glyoxal thereto, and mechanically stir at room temperature until the mixture is uniformly mixed to obtain a lignin-based non-isocyanate polyurethane adhesive. The sample is recorded as LNIPUs-G3.
[0070] Example 4: Preparation of high performance lignin-based non-isocyanate polyurethane adhesive (LNIPU-G4) based on transesterification-aldehyde amine chemistry The lignin is enzymatically hydrolyzed lignin, the non-cyclic diester compound is dimethyl carbonate, the polyamine is polyetheramine, and the cross-linking agent is 50% glutaraldehyde aqueous solution.
[0071] (1) Add 30 g of enzymatically hydrolyzed lignin, 20 g of dimethyl carbonate (DMC), and 30 g of sodium hydroxide aqueous solution with a pH of 9 to 14 into a 500 mL three-necked flask, stir and mix, and react at 50 ° C for 1.5 h to 2 h under mechanical stirring. Add 30 g of polyetheramine to the above solution, raise the temperature to 90 ° C, and react for 4 h to prepare lignin-based non-isocyanate prepolymer (LNIPUs).
[0072] (2) Weigh 30 g of the LNIPUs solution obtained in step (1) into a plastic cup, add 6 g of a 50% glutaraldehyde aqueous solution thereto, and mechanically stir at room temperature until the mixture is uniformly mixed to obtain a lignin-based non-isocyanate polyurethane adhesive. The sample is recorded as LNIPUs-G4.
[0073] Comparative Example 1: Preparation of adhesive sample (LNIPUs-1) without adding polyamine (Control Group 1) The lignin is enzymatically hydrolyzed lignin, the non-cyclic diester compound is dimethyl carbonate, and the cross-linking agent is 50% glutaraldehyde aqueous solution.
[0074] (1) Add 30 g of enzymatically hydrolyzed lignin and 30 g of a sodium hydroxide aqueous solution with a pH of 9 to 14 into a 500 mL three-necked flask, stir and mix well, and react at 50°C with mechanical stirring for 1.5 h to 2 h.
[0075] (2) Weigh 30 g of the solution obtained in step (1) into a plastic cup, add 6 g of a 50% glutaraldehyde aqueous solution thereto, and mechanically stir at room temperature until the mixture is uniformly mixed to obtain control group sample 1.
[0076] Comparative Example 2: Preparation of a sample of adhesive modified without adding a crosslinking agent (LNIPUs-2) (Control Group 2) The lignin is enzymatically hydrolyzed lignin, the non-cyclic diester compound is dimethyl carbonate, and the polyamine is polyetheramine.
[0077] Add 30g of enzymatic lignin, 20g of dimethyl carbonate (DMC), and 30g of sodium hydroxide aqueous solution with a pH of 9 to 14 into a 500mL three-necked flask, stir and mix well, and react at 50°C with mechanical stirring for 1.5h to 2h. Add 30g of polyetheramine to the above solution, raise the temperature to 90°C, and react for 4h to obtain control sample 2.
[0078] Comparative Example 3: Preparation of a sample of adhesive without adding lignin (LNIPUs-3) (Control Group 3) The non-cyclic diester compound is dimethyl carbonate, the polyamine is polyetheramine, and the cross-linking agent is 50% glutaraldehyde aqueous solution.
[0079] (1) Add 20 g of dimethyl carbonate (DMC), 30 g of sodium hydroxide aqueous solution with a pH of 9 to 14, and 30 g of polyetheramine to a 500 mL three-necked flask, raise the temperature to 90°C, and react for 4 h.
[0080] (2) Weigh 30 g of the solution obtained in step (1) into a plastic cup, add 6 g of a 50% glutaraldehyde aqueous solution thereto, and mechanically stir at room temperature until the mixture is uniformly mixed, to obtain control group sample 3.
[0081] Comparative Example 4: Preparation of lignin-based non-isocyanate polyurethane adhesive under acidic conditions (LNIPUs-4) (Control Group 4) The lignin is enzymatically hydrolyzed lignin, the non-cyclic diester compound is dimethyl carbonate, the polyamine is polyetheramine, and the cross-linking agent is 50% glutaraldehyde aqueous solution.
[0082] (1) Add 30 g of enzymatically hydrolyzed lignin, 20 g of dimethyl carbonate (DMC), and 30 g of hydrochloric acid aqueous solution with a pH of 3 to 6 to a 500 mL three-necked flask, stir and mix, and react at 50 ° C for 1.5 h to 2 h under mechanical stirring. Add 30 g of polyetheramine to the above solution, raise the temperature to 90 ° C, and react for 4 h to prepare lignin-based non-isocyanate prepolymer (LNIPUs).
[0083] (2) Weigh 30 g of the LNIPUs solution obtained in step (1) into a plastic cup, add 6 g of a 50% glutaraldehyde aqueous solution thereto, and mechanically stir at room temperature until the mixture is uniformly mixed, to obtain control group sample 4.
[0084] Comparative Example 5: Preparation of lignin-based non-isocyanate polyurethane adhesive under neutral conditions (LNIPUs-5) (Control Group 5) The lignin is enzymatically hydrolyzed lignin, the non-cyclic diester compound is dimethyl carbonate, the polyamine is polyetheramine, and the cross-linking agent is 50% glutaraldehyde aqueous solution.
[0085] (1) Add 30 g of enzymatically hydrolyzed lignin, 20 g of dimethyl carbonate (DMC), and 30 g of sodium chloride solution with a pH of 7 into a 500 mL three-necked flask, stir and mix, and react at 50 °C under mechanical stirring for 1.5 h to 2 h. Add 30 g of polyetheramine to the above solution, raise the temperature to 90 °C, and react for 4 h to prepare lignin-based non-isocyanate prepolymer (LNIPUs).
[0086] (2) Weigh 30 g of the LNIPUs solution obtained in step (1) into a plastic cup, add 6 g of a 50% glutaraldehyde aqueous solution thereto, and mechanically stir at room temperature until the mixture is uniformly mixed to obtain control group sample 5.
[0087] Comparison of viscosity of different lignin-based non-isocyanate polyurethane adhesives The apparent viscosity of the adhesive was obtained using a rotational viscometer (NDJ-5S, Lichen, Shanghai, China) at room temperature with an appropriate rotor and speed. Each sample was tested three times and the average value was recorded. The obtained viscosity test results are shown in Table 1.
[0088] Table 1 Comparison of viscosity of different adhesives
[0089] As can be seen from Table 1, the control group did not contain any adhesive containing lignin, and the overall molecular weight was low, resulting in the lowest viscosity of 194 mPa∙s. In addition, in the control groups 4 and 5, since lignin could not dissolve in acidic conditions and could not undergo ester exchange reaction with dimethyl carbonate, a large amount of lignin powder floated on the solution during the viscosity test. Figure 1It can be concluded from the preparation process of the adhesive that the adhesives using different lignins formed a dense cross-linked network after being modified with an aldehyde cross-linking agent, so the viscosity of the adhesive gradually increased. The viscosity of Example 4 was as high as 5521 mPa∙s. It can be seen that the chemical cross-linking of aldehyde amine is effective in modifying the adhesive, and the viscosity and molecular weight gradually increase with the increase of the aldehyde cross-linking agent.
[0090] Comparison of water absorption properties of different lignin-based non-isocyanate polyurethane adhesives Table 2 Comparison of water absorption of different adhesives after immersion for 10 hours
[0091] Under humid conditions, the water resistance of the adhesive plays an important role in the bonding performance and application life of the adhesive. The water absorption performance test is to soak the cured adhesive in water and calculate the weight change at a certain time interval. As shown in Table 2, Figure 3 As shown, the cured adhesive exhibits different water absorption rates when immersed in water. Comparative Examples 1 and 2 absorb a large amount of water in a short period of time when immersed in water, and then most of the adhesive is dispersed or dissolved in water. Although the data shows that the water absorption rate decreases, the adhesive actually has poor water resistance. Comparative Example 3 is dissolved in water and does not have water resistance. Comparative Examples 4 and 5 cannot be tested because the lignin cannot be dissolved and the adhesive quickly disperses in water in a powdery state. Compared with the control group samples, the adhesive modified by aldehyde cross-linking has a hyperbranched cross-linked network and therefore has excellent water resistance, among which Example 4 has the smallest water absorption rate and the best water resistance.
[0092] Comparison of water contact angles of different lignin-based non-isocyanate polyurethane adhesives The contact angle test was performed using a drop shape analyzer (DSA100, KRÜSS, Germany) with a 2 μL water droplet. Figure 4 The surface contact angle bar graphs and water droplet profile graphs of the adhesives prepared in Examples 1 to 4 and Comparative Examples 1 to 3 are given. Comparative Examples 4 to 5 could not be tested because lignin could not be dissolved. Figure 4 As can be seen, the control group sample exhibits the smallest water contact angle, while the lignin-based non-isocyanate adhesive modified by aldehyde cross-linking has excellent hydrophobicity, and the water contact angle (CA) of Example 4 is 80°. Figure 2 This is the bonding mechanism of high-performance lignin-based non-isocyanate polyurethane adhesives. The hydrophobic groups in lignin also give the adhesive excellent hydrophobicity.
[0093] Solid-state NMR characterization of high-performance lignin-based non-isocyanate polyurethane adhesive Solid state nuclear magnetic resonance characterization was performed using a nuclear magnetic resonance instrument (Avance Neo 400 MHz NMR, Bruker, Germany) to test lignin, comparative example 1, and example 4. Figure 5 It can be seen that the signal at 151 ppm is a typical peak of carbamate bonds, which confirms the successful synthesis of carbamate bonds. The 48 ppm signal appearing in the spectrum of LNIPUs-G proves that glutaraldehyde can react with LNIPUs to form CN bonds. This proves our successful synthesis of carbamate bonds and the successful modification of adhesives with aldehyde crosslinkers.
[0094] Fourier infrared characterization of high performance lignin-based non-isocyanate polyurethane adhesive Fourier infrared characterization was performed using a Fourier infrared spectrometer (Spectrum 100, USA). Figure 6 The 1659 cm -1 and 1549cm -1 The peaks at 1549cm-1 in LNIPUs belong to C=O and NH in the carbamate bond. The appearance of these two peaks proves the successful synthesis of the carbamate bond. -1 The peak at disappeared, and a peak belonging to the amide group was found, which proved that the aldehyde cross-linking agent can undergo cross-linking reaction with the prepolymer LNIPUs.
[0095] Three-layer plywood bonding strength performance test The shear strength of three-layer plywood is tested according to the national standard GB / T 17657-2022. The specific data are shown in Table 3.
[0096] Table 3 Comparison of bonding properties of different lignin-based non-isocyanate adhesives
[0097] From Table 3 and Figure 7 It can be seen that the dry bonding strength of control groups 1, 2, 4, and 5 is only 0.43MPa and 0.82MPa, and the water resistance is very poor, which does not meet the requirements of type II plywood. Comparative Example 3 does not have bonding performance, and comparative examples 4 and 5 have poor bonding strength because the lignin is insoluble and no reaction occurs. However, the dry bonding strength of Example 4 reaches 1.96MPa, the type II wet bonding strength reaches 1.68MPa, and it meets the requirements of type I plywood at 1.32MPa, meets the standards of outdoor plywood, and has excellent bonding properties.
[0098] from Figure 7It can be seen from the comparison diagram of wood damage of several comparative examples and embodiments that since comparative example 3 does not have bonding performance and comparative examples 4 and 5 have very poor bonding strength, there is no wood damage. The high-performance lignin-based non-isocyanate polyurethane adhesive prepared by the present invention effectively improves the water resistance and bonding strength of plywood. Due to the cross-linking reaction between aldehyde and adhesive, the viscosity of the adhesive increases, which better penetrates into the interior of the wood to form a larger contact area, thereby improving the bonding strength. In addition, the cohesive force of the adhesive itself is much higher than that of the wood itself, resulting in a gradual increase in the wood damage rate.
[0099] Figure 8 The penetration of several comparative examples and embodiments in plywood shows that, for adhesives, the increase in viscosity is also beneficial to enhancing the coating and permeability of adhesives on wood veneers, thereby increasing the bonding strength of plywood. Example 4 has the best permeability. According to the previous viscosity test results, since adhesives with lower viscosity have higher fluidity, they are squeezed out during the hot pressing process and cannot form a complete adhesive layer on the interface. Example 4 with the highest viscosity can form a more complete adhesive layer on the interface, thereby improving the bonding strength of plywood.
[0100] Bonding properties of high-performance lignin-based non-isocyanate polyurethane adhesive to different substrates In order to demonstrate the multifunctional bonding performance of the high-performance lignin-based non-isocyanate polyurethane adhesive, Example 4 was used to bond different substrates, such as Fig. 9 As shown, the specimen used for the shear strength test is composed of a 312.5mm 2 The sample was placed at 180°C for 2 hours and then tested with a universal mechanical testing machine (BY302X2 / 2) at a shear rate of 5 mm / min. The test results are shown in Table 4 and Fig. 9 shown.
[0101] Table 4 Comparison of bonding performance of high-performance lignin-based non-isocyanate polyurethane adhesives on different substrates
[0102] From Table 4 and Fig. 9 It can be seen that Example 4 has universal adhesion to various organic and inorganic materials, which shows that the adhesive is suitable for bonding various substrates, providing a wider range of applications for the adhesive. Figure 2 The adhesive bonding mechanism shows that the reason for the universal adhesion is that the hard segments provided by lignin and the soft segments provided by polyetheramine are cross-linked, providing strong cohesive force for the adhesive. In addition, the high-density hydrogen bonds formed at the bonding interface give the adhesive excellent adhesion on various substrates.
[0103] The adhesion performance of Example 4 and commercial polyurethane (purchased from Guangdong Aoxinda Company) on different substrates was compared. Fig.10 It can be seen that the bonding performance of Example 4 is comparable to that of commercial polyurethane adhesives on the market. Therefore, the adhesive of the present invention is expected to replace commercial polyurethane adhesives.
[0104] Test on organic solvent resistance of high performance lignin-based non-isocyanate polyurethane adhesive In order to demonstrate the organic solvent resistance of high-performance lignin-based non-isocyanate polyurethane adhesive, the iron was bonded using Example 4 and then immersed in different organic solvents for 168 hours. The preparation method of the sample is the same as the bonding performance test of different substrates. The prepared sample was then tested with a universal mechanical testing machine (BY302X2 / 2) at a shear rate of 5 mm / min. The test results are shown in Table 5 and Fig.11 shown.
[0105] Table 5 Comparison of bonding properties of adhesives immersed in different organic solvents
[0106] It can be seen from Table 5 that the iron joint still maintains more than 80% of the shear strength after being immersed in different organic solvents for 168 h. Since the adhesive has a hyperbranched cross-linked network, a stable structure, and a high hydrogen bond density, it has excellent resistance to organic solvents. Figure 2 The bonding mechanism also explains this reason. It can be seen from this that the adhesive provided by the present invention has excellent resistance to organic solvents and is suitable for a variety of use environments.
[0107] Low temperature resistance test of high performance lignin-based non-isocyanate polyurethane adhesive We also tested the low temperature resistance of the adhesive. The iron pieces bonded by Example 4 were placed in low temperature environments of 4°C, -10°C, -20°C, -30°C and -50°C for 12 hours, and then kept at room temperature for shear strength testing. The test results are shown in Figure 2. Fig.12 shown.
[0108] The shear strength of the specimen placed at 4°C can still maintain 10.08MPa. As the temperature decreases, although the bonding performance of the adhesive decreases, it still shows a high shear strength. The shear strength of the specimen placed at -50°C still remains more than 70% of that before placement. The structural stability and high-density hydrogen bonds of the adhesive improve the low-temperature resistance and inhibit brittle failure. It can be seen that the adhesive prepared by the present invention has excellent low-temperature resistance and can be used for a long time in special environments.
[0109] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A high-performance lignin-based non-isocyanate polyurethane adhesive, characterized in that: Prepared by the following method: 1) Dissolve lignin in an aqueous solution with a pH of 9 to 14, and heat and stir to obtain an alkaline lignin solution; 2) adding a non-cyclic diester compound to the alkaline lignin solution obtained in step 1) to carry out an ester exchange reaction to obtain an esterified lignin solution; 3) adding polyamine to the esterified lignin solution obtained in step 2), stirring and mixing to carry out polycondensation reaction, and obtaining a lignin-based non-isocyanate prepolymer solution; 4) Adding a cross-linking agent to the lignin-based non-isocyanate prepolymer solution obtained in step 3), stirring and mixing the mixture evenly, and discharging the mixture to obtain the high-performance lignin-based non-isocyanate polyurethane adhesive.
2. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 1, characterized in that: The mass ratio of lignin to aqueous solution is 1:3 to 3:1; and / or The mass ratio of the aqueous solution to the non-cyclic diester compound is 1:4 to 3:1; and / or The mass ratio of the non-cyclic diester compound to the polyamine is 1:3 to 4:1; and / or The mass ratio of the polyamine to the cross-linking agent is 1:5 to 5:
1.
3. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 1, characterized in that: The transesterification reaction conditions in step 2) are: 40-90° C., reaction time 20-150 min; and / or The polycondensation reaction conditions in step 3) are: 70-99° C., reaction time 20-240 min; and / or The cross-linking reaction conditions in step 4) are: 0-50° C., and the reaction time is 1-30 min.
4. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 1, characterized in that: The lignin in step 1) is selected from at least one of alkali lignin, enzymatic lignin, Kraft lignin, lignin sulfonate, and organic solvent lignin.
5. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 1, characterized in that: The aqueous solution in step 1) is selected from at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide aqueous solutions.
6. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 1, characterized in that: The general structural formula of the non-cyclic diester compound in step 2) is , , wherein R1, R2, R3, R5 are alkyl groups, R4 is -CH2-, and the number of R4 is an integer greater than or equal to 1.
7. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 1, characterized in that: The general structural formula of the polyamine in step 3) is: , , , , , , where m, n, s, p, t, and k are all integers greater than or equal to 1.
8. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 1, characterized in that: The general structural formula of the cross-linking agent in step 4) is (R7) y -R6-(R8) x , wherein x and y are integers greater than or equal to 1, R7 and R8 are functional groups that can react with amino groups, and R6 is a connecting structure.
9. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 8, characterized in that: R7 and R8 are relatively independent aldehyde groups.
10. The high performance lignin-based non-isocyanate polyurethane adhesive according to claim 8 or 9, characterized in that: The cross-linking agent in step 4) is selected from at least one of glutaraldehyde, glyoxal, malondialdehyde, suberaldehyde and dialdehyde starch.
Citation Information
Patent Citations
Preparation method of degradable polycarbonate type lignin-based oil-displacing agent monomer
CN104292446A
Modified lignin and preparation method thereof
CN111961221A
Non-isocyanate polyurethanes from bio-based polyols
CN116323738A
Environment-friendly bio-based polyurethane adhesive and preparation method thereof
CN115305041A
Aminated lignin-soybean protein composite adhesive as well as preparation method and application thereof
CN117343692A
Cited By
Organic acid ester modified lignin phenolic resin adhesive and preparation method thereof
CN120554995A